2020
DOI: 10.1016/j.neuron.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Usp9X Controls Ankyrin-Repeat Domain Protein Homeostasis during Dendritic Spine Development

Abstract: Variants in the ANK3 gene encoding ankyrin-G are associated with neurodevelopmental disorders, including intellectual disability, autism, schizophrenia, and bipolar disorder. However, no upstream regulators of ankyrin-G at synapses are known. Here, we show that ankyrin-G interacts with Usp9X, a neurodevelopmental-disorder-associated deubiquitinase (DUB). Usp9X phosphorylation enhances their interaction, decreases ankyrin-G polyubiquitination, and stabilizes ankyrin-G to maintain dendritic spine development. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 64 publications
2
45
0
Order By: Relevance
“…Many of these 42 variants were inherited through unaffected mothers, while others arose de novo. We showed that these male USP9X missense variants cause partial, rather than complete loss of USP9X function 7,8,11 . In particular, these mutations disable brain-specific USP9X functions, while leaving other functions, such as those essential for embryonic viability, intact.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Many of these 42 variants were inherited through unaffected mothers, while others arose de novo. We showed that these male USP9X missense variants cause partial, rather than complete loss of USP9X function 7,8,11 . In particular, these mutations disable brain-specific USP9X functions, while leaving other functions, such as those essential for embryonic viability, intact.…”
Section: Introductionmentioning
confidence: 83%
“…Male USP9X variants in the N-terminal regions have been shown to disrupt subsets of USP9X substrate interactions, rather than all 7 . These substrates are, however, critical specifically for the function of neurodevelopmental signalling pathways TGFβ, mTOR, Notch and Wnt 7 , all of which have been shown to be deregulated in the developing brains of mice lacking Usp9x 11,37,[41][42][43] . It was also striking to see that males shared much of the neurological phenotypical features shared in our female cohorts, but almost none of the other congenital features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, growing evidence has shown that specific neuronal cell types contribute to the mechanisms of behavioral changes in ASD animal models (Tyzio et al, 2014;Bariselli et al, 2016;Zhang Y. et al, 2016;Wang et al, 2017;Guo et al, 2019). Moreover, a considerable number of studies have suggested an association between ASDs and dendritic spine abnormalities involving different stages, such as spine development, maturation, elimination, and pruning (Tang et al, 2014;Yadav et al, 2017;Yoon et al, 2020). Therefore, it is essential to characterize the morphological changes of distinct cell types in the brain circuits of those animal models of disease, which will greatly help us to understand the etiology of ASD, especially dendritic processes and dendritic spines.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Usp9x -/Y;Emx1-Cre mice were further showed hyperactive behaviour in two assays, the elevated plus maze and light-dark box tests (Yoon et al, 2020). Future experiments should also examine whether Usp9x -/Y;Emx1-Cre mice model autistic-like traits, reminiscent of USP9X-deficient patients.…”
Section: Discussionmentioning
confidence: 96%